The Effect of Adenosine Phosphates on the Spreading of Normal Human Platelets - Linker, H; Reuter, H (Thrombosis and Haemostasis, 1969)
The spreading of human platelets requires the presence of ADP as do other platelet functions. In the plasma of patients with a failure of release of ADP from the platelets the also decreased ability to spread can be normalized by exogenous ADP. AMP and ATP inhibit the spreading of platelets.